Pulmonary function decreases moderately after accelerated high‐dose irradiation for stage III non‐small cell lung cancer. Issue 2 (19th December 2019) - Grambozov, Brane; Wolf, Frank; Kaiser, Julia; Wass, Romana; Fastner, Gerd; Gaisberger, Christoph; Rettenbacher, Lukas; Studnicka, Michael; Pirich, Christian; Sedlmayer, Felix; Zehentmayr, Franz
Abstract: Background: Chemoradiotherapy (CRT) is the standard treatment for patients with inoperable stage III non‐small cell lung cancer (NSCLC) stage III. With a median OS beyond 30 months, adequate pulmonary function (PF) is essential to ensure acceptable quality of life after treatment. Forced expiratory volume in 1 second (FEV1) and diffusing capacity of the lung for carbon monoxide (DLCO) are the most widely used parameters to assess lung function. The aim of the current study was to evaluate dose‐volume effects of accelerated high‐dose radiation on PF. Methods: A total of 72 patients were eligible for the current analysis. After induction chemotherapy, all patients received dose‐differentiated accelerated radiotherapy with intensity‐modulated radiotherapy (IMRT‐DART). PF tests were performed six weeks, three and six months after the end of radiotherapy. Results: The median total dose to the tumor was 73.8 Gy (1.8 Gy bid) with a size dependent range between 61.2 and 90 Gy. In the whole cohort, 321 pulmonary function tests were performed. At six months, the median FEV1 relative to baseline was 0.95 (range: 0.56–1.36), and the relative median DLCO decreased to 0.98 (range: 0.64–1.50). The correlation between V20total lung and FEV1 decline was statistically significant ( P = 0.023). A total of 13 of 34 (38%) COPD patients had a 4%–21% FEV1 decrease. Conclusion: Patients with a V20total lung < 21% are at a low risk for PF decrease after high dose irradiation treatment. Although overall short term FEV1 and DLCO differ only moderately from baseline these changes may be clinically important, especially in patients with COPD. Key points: Significant findings: Pulmonary function after high dose irradiation decreases only moderately. FEV1 and DLCO decrease depend on V20total lung . Small differences in lung function may be clinically important for COPD patients. KPS predicts minimal clinically important differences (MCID). What this study adds: This study shows that high‐dose irradiation delivered with intensity‐modulated techniques does not impair short‐term lung function even in patients with compromised respiratory capacity before treatment. This is a pre‐requisite for adequate quality of life after thoraco‐oncological therapy.